Auxetic-Inspired Honeycomb Macrostructures With Anomalous Tailormade Thermal Expansion Properties Including “Negative” Heat-Shrinking Characteristics - Grima-Cornish, James N.; Attard, Daphne; Evans, Kenneth E.; Grima, Joseph N. (Frontiers in Materials, 2021)
Negative thermal expansion (NTE) materials and structures exhibit the anomalous property of shrinking rather than expanding when heated. This work examines the potential of multi-material planar re-entrant and non-re-entrant honeycombs to exhibit anomalous thermal expansion properties. Expressions for the coefficient of thermal expansion as a function of the geometric parameters and intrinsic thermal expansion properties were derived for any in-plane direction. It was shown that re-entrant honeycombs, a metamaterial which is well known for its auxetic characteristics, can be made to exhibit NTE in specific directions when constructed from conventional positive thermal expansion (PTE) materials, provided that the slanting ligaments expand more than the vertical ligaments when heated and that the geometry is amenable. Conversely, it was shown that the construction of such honeycombs from NTE components will not necessarily result in a system which exhibits NTE in all directions. Furthermore, conditions which result in honeycombs demonstrating zero thermal expansion (ZTE) coefficients in specific directions were also explored.